2002
DOI: 10.2223/jped.900
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous surfactant therapy - what is established and what still needs to be determined

Abstract: Objetivo: revisar os aspectos já consagrados da terapêutica com surfactante exógeno, e discutir o estágio atual da pesquisa onde ainda não existe consenso. Fonte dos dados: revisão bibliográfica, utilizando o banco de dados Medline e Cochrane Database Library, associada à experiência dos autores em relação à terapêutica de reposição do surfactante exógeno. Síntese dos dados: os aspectos principais em relação às características do surfactante: composição, pool, metabolismo, inativação e efeitos imediatos após s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
1
0
4
Order By: Relevance
“…Rebello et al demonstrated a reduction in the mortality rate of these infants of up to 40%. 1 Chotigeat et al in Thailand demonstrated a mortality rate of 18% in a group of patients treated with surfactant, 7 and Kirsten et al in South Africa demonstrated a survival rate of 63% in patients who received SRT. 13 However, other studies like our study have documented no increase in survival of preterm infants with RDS with the use of surfactant.…”
Section: Outcome Of Patients Receiving Surfactant Replacement Therapymentioning
confidence: 99%
“…Rebello et al demonstrated a reduction in the mortality rate of these infants of up to 40%. 1 Chotigeat et al in Thailand demonstrated a mortality rate of 18% in a group of patients treated with surfactant, 7 and Kirsten et al in South Africa demonstrated a survival rate of 63% in patients who received SRT. 13 However, other studies like our study have documented no increase in survival of preterm infants with RDS with the use of surfactant.…”
Section: Outcome Of Patients Receiving Surfactant Replacement Therapymentioning
confidence: 99%
“…Apesar dos avanços significativos ocorridos nos cuidados intensivos neonatais nas últimas décadas, como a utilização de corticosteroides no período pré-natal, a administração de surfactante, que minimizou a severidade da lesão pulmonar em prematuros, o uso de estratégias protetoras de ventilação mecânica e a melhora da nutrição (Rebello et al, 2002;Speer, 2003;Mataloun et al, 2005), observou-se um aumento na incidência da DBP em decorrência da maior sobrevida de prematuros cada vez mais extremos (Hack e Fanaroff, 1999;Bancalari et al, 2003;Deakins, 2009). A incidência da DBP é variável, ficando em torno de 20% nos prematuros que necessitam de ventilação mecânica.…”
Section: Displasia Broncopulmonarunclassified
“…O desenvolvimento pulmonar humano é dividido em cinco fases: embrionária, pseudoglandular, canalicular, sacular e alveolar (Jobe, 2002;Coalson, 2003). A fase embrionária começa com o início da gestação e se estende até a sétima semana de vida intrauterina.…”
Section: Fases Do Desenvolvimento Pulmonarunclassified
See 2 more Smart Citations